Learning from their Own History An Analysis of the Leader’s Speech in the Book of Samuel - Bîrle, Samuel F. (2022)
The final speech given by Samuel to mark the passing from a theocratic to a monarchical regime is distinguished by the strategy of learning from their own history. The leader uses historical elements to determine the community to obey Yahweh as a part of an educational strategy whereby the leader uses history for pedagogical purposes. The mentioned events are subjective in nature and reflect the re-validation of Samuel as leader, the belief that Saul had become a part of the divine plan of government, and it highlights the sins of the people showing the decisive contribution of Yahweh to the progress of the community up until that moment.
Keywords: Samuel; Education; History; Leadership; Speech; Strategy